2011
DOI: 10.1016/j.bbamem.2011.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PAMAM-OH dendrimers on the activity of human erythrocytes ATPases

Abstract: Dendrimers are a relatively new and still not fully examined group of polybranched polymers. In this study polyamidoamine dendrimers with hydroxyl surface groups (PAMAM-OH) of third, fourth and fifth generation (G3, G4 and G5) were examined for their ability to influence the activity of human erythrocyte plasma membrane adenosinetriphosphatases (ATPases). Plasma membrane ATPases are a group of enzymes related, among others, to the maintenance of ionic balance inside the cell. An inhibition of their activity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
0
21
0
2
Order By: Relevance
“…PAMAM-NH 2 , one of the cationic dendrimers, is a positively charged particle, because of the protonation equilibria (Cakara et al, 2003;Cakara and Borkovec, 2007). In contrast, PAMAM-OH dendrimers did not affect the activity of human erythrocyte ATPase (Ciolkowski et al, 2011b), but positively surface-charged polystyrene particles induced platelet aggregation (Mayer et al, 2009;Dobrovolskaia et al, 2012). These reports suggest that dendrimer-induced cytotoxicity may cause by the surface charge of the dendrimers.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…PAMAM-NH 2 , one of the cationic dendrimers, is a positively charged particle, because of the protonation equilibria (Cakara et al, 2003;Cakara and Borkovec, 2007). In contrast, PAMAM-OH dendrimers did not affect the activity of human erythrocyte ATPase (Ciolkowski et al, 2011b), but positively surface-charged polystyrene particles induced platelet aggregation (Mayer et al, 2009;Dobrovolskaia et al, 2012). These reports suggest that dendrimer-induced cytotoxicity may cause by the surface charge of the dendrimers.…”
Section: Discussionmentioning
confidence: 47%
“…The effect of surface modifications to PAMAM dendrimers on their cytotoxicity has been studied previously (Hernando et al, 2012;Ciolkowski et al, 2011b), and amine-terminated (NH 2 ) PAMAM dendrimers were associated with a higher cytotoxic response. The effect of PAMAM dendrimer generation on their cytotoxicity was also investigated using an in vitro experiment that examined high-generation (G4, G5, and G6) PAMAM dendrimers (Mukherjee et al, 2010a(Mukherjee et al, , 2010bMaher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…70 This activity may also depend on the type of dendrimer generated. 71 Nanoparticle interactions with erythrocytes cause abnormal membrane proteins and lipids that lead to the destruction of erythrocyte integrity and hemolysis. To investigate why some curcumin formulations are toxic to erythrocytes at 100 µM, binding of nanoparticles and red blood cells was investigated using transmission electron microscopy.…”
Section: Hemolysismentioning
confidence: 99%
“…71 Altogether, these results provide an interesting insight into the correlation between various curcumin nanoformulations and protein interactions that may impact in vivo efficacy. From the analysis of protein binding and hemolysis experiments, it can be concluded that all the curcumin nanoformulations behave differently than the dendrimer curcumin formulation.…”
mentioning
confidence: 99%
“…Technique adapted for performing Zeta Potential was Dynamic Light Scattering Technique. The values of Zeta potential for Econazole loaded dendrimers ranged from -37 to -48, indicating good stability of the formulations (Ciolkowski et al, 2011). Stability of the formulations is contributed to the smaller dendritic size and repulsive electrostatic forces of dendrimers (Table no.4).…”
Section: Zeta Potentialmentioning
confidence: 99%